Bilateral Medial Rectus Advancement versus Unilateral Medial Rectus Advancement with Lateral Rectus Recession for Surgical Management of Large Angle Consecutive Exotropia without Adduction Deficit - Abdelaziz STA; Ibrahiem MFK (Clinical Ophthalmology, 2022)
Sahar Torky Abdelrazik Abdelaziz, Mohamed Farag Khalil Ibrahiem Ophthalmology Department, Faculty of Medicine, Minia University, Minia, EgyptCorrespondence: Sahar Torky Abdelrazik Abdelaziz, Ophthalmology Department, Minia University Hospital, Minia University, 98 Cornish El Nile Street, Minia, 61111, Egypt, Tel +201065716074, Email sahar.abdelrazek@mu.edu.eg; sahar.torky@yahoo.comPurpose: To compare the postoperative eye alignment in patients who underwent bilateral medial rectus advancement with those who underwent unilateral medial rectus advancement plus ipsilateral lateral rectus recession in the case of large angle consecutive exotropia without adduction deficit.Methods: Thirty-four patients with large angle consecutive exotropia that developed after infantile esotropia surgery were included in this retrospective study. Nineteen patients underwent bilateral medial rectus muscle advancement (group I) and 15 underwent unilateral medial rectus muscle advancement with ipsilateral lateral rectus muscle recession (group II). The follow-up periods were at least 12 months. Postoperative eye alignment was assessed and orthotropia within 10 prism diopters was considered a successful result.Results: The mean age of patients was 9.45± 2.71 years in group I and 9.93± 2.05 years in group II. Sixty percent of patients were female in group II and 57.89% in group I. In group I, the mean preoperative angle of deviation was 56.26± 3.78 PD at distance and 53.11± 3.49 PD at near. In group II, patients had a mean preoperative angle of deviation of 56± 3.38 and 52.47± 2.77 PD at distance and near, respectively. At the end of the follow-up period, the success rate was 52.63% in group I and 73.33% in group II (p = 0.22). The mean of the dose-effect relationship in group I was 2.62± 1.35 PD/mm while in group II it was 2.36± 0.84 PD/mm (p = 0.52).Conclusion: In patients with large angle consecutive exotropia, unilateral medial rectus advancement combined with ipsilateral lateral rectus recession produced better postoperative eye alignment than bilateral medial rectus advancement. Group I had a higher dose-effect relationship than group II.Keywords: consecutive exotropia, large angle, medial rectus advancement, lateral rectus recession